Signal transduction pathways and transcriptional regulation in Th17 cell differentiation - Hirahara, Kiyoshi (2010)
Over the last decade, our understanding of helper/effector T cell differentiation has changed dramatically. The discovery of interleukin (IL-)17–producing T cells (Th17) and other subsets has changed our view of T cell-mediated immunity. Characterization of the signaling pathways involved in the Th17 commitment has provided exciting new insights into the differentiation of CD4(+) T cells. Importantly, the emerging data on conversion among polarized T helper cells have raised the question how we should view such concepts as T cell lineage commitment, terminal differentiation and plasticity. In this review, we will discuss the current understanding of the signaling pathways, molecular interactions, and transcriptional and epigenetic events that contribute to Th17 differentiation and acquisition of effector functions.